When to start antiretroviral therapy in resource-limited settings. - Walensky, Rochelle P; Wolf, Lindsey L; Wood, Robin; Fofana, Mariam O; Freedberg, Kenneth A; Martinson, Neil A; Paltiel, A David; Anglaret, Xavier; Weinstein, Milton C; Losina, Elena (Annals of internal medicine, 2009)
The results of international clinical trials that are assessing when to initiate antiretroviral therapy (ART) will not be available for several years.
Keywords: Adult; AIDS-Related Opportunistic Infections; Anti-HIV Agents; Anti-Infective Agents; CD4 Lymphocyte Count; Cohort Studies; Computer Simulation; Cost-Benefit Analysis; Decision Trees; Disease Progression; Drug Administration Schedule; Health Care Costs; HIV Infections; Humans; Life Expectancy; Sensitivity and Specificity; South Africa; Trimethoprim-Sulfamethoxazole Combination